THE INFLUENCE OF PRICE, PROMOTION, AND PRODUCT QUALITY ON CONSUMER SATISFACTION WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Mutia Arda; Dewi Andriany (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Abstract*